Paediatric Residents Training in Pakistan: Time for a Paradigm Shift - Muhammad Tawab Khalil; Sana Arshad; Farooq Azam Rathore (Journal of the Pakistan Medical Association, 2023)
Dear Editor, We have read the editorial titled “Paediatric Residents Training in Pakistan: Time for a Paradigm Shift” by Mehnaz A. with interest.1 The author has correctly highlighted the lack of competency based curriculum for training in paediactrics in Pakistan. It is estimated that 34% of population of Pakistan is below the age of 14 years.1 Nationwide data regarding childhood disability in Pakistan is scarce and mostly limited to hospital based surveys only.2 Continue...